Elective Intermittent Temporary Clipping in Aneurysm Surgery: A Practical Protocol - Selvapandian, S.; Sudarsan, P. Sai; Shaji, Pannakal G.; Chandy, Mathew J. (Indian Journal of Neurosurgery, 2015)
Background Temporary occlusion of the proximal vessel is being increasingly used as an adjunct during aneurysm surgery for safer dissection, evacuation of the aneurysm, and to prevent intraoperative rupture. The guidelines regarding its practice are ambiguous. One of the major concerns is the safe time limit for temporary occlusion. Studies done so far have failed to reach a consensus on this issue. This study is an attempt to provide a practical, safe time period of intermittent occlusion of an artery in the anterior circulation, irrespective of vascular territory.Patients and Methods A total of 68 patients in whom elective, intermittent, temporary clipping of the proximal vessel was employed during aneurysm surgery were prospectively studied. They were divided into two groups, Group I with an occlusion period of less than 7 minutes and Group II with occlusion period of 10 minutes and above per episode. The incidence of complications in both groups, their relationship to the number of intermittent clippings, and the total duration of clipping were analyzed.Results The incidence of complications was more in Group II (23.5 vs. 8.8%). There was a reduction in the incidence of complications when the duration of occlusion per episode was reduced; this, however, was not reflected statistically (p = 0.1). The total duration of temporary occlusion, when compared, was significantly longer in Group II (p = 0.000). The total duration of clipping, however, was not significantly different between those who developed complications and those who did not (p = 0.86). The occurrence of complications did not correlate with the vascular territory, number of intermittent clippings, or the total duration of occlusion within their respective groups.Conclusion Our study supports the view that the proximal vessel can be safely occluded during aneurysm surgery. The total occlusion period could be safely prolonged when employed in an intermittent fashion with periods of reperfusion to attain the objective of safe dissection. The reduction in duration of each episode of occlusion, though resulted in fewer complications, did not reach statistical significance.
Keywords: aneurysm surgery; temporary occlusion; elective; intermittent; time limit